James Baldwin's Decolonial Love as Religious Orientation - Drexler-Dreis, Joseph (Journal of Africana religions, 2015)
In this article, I use the concept of decolonial love to synthesize the religious and theological dimensions of James Baldwin's work. I argue that Baldwin's decolonial love functions as an ultimate orientation within his work, and that decolonial love is an orientation and a praxis that is a form of revelation. The revelatory capacity of decolonial love, which particularly comes out of the lived experiences on the underside of Western modernity, catalyzes what Baldwin refers to as salvation. I show this, first, by engaging Baldwin's decolonial love as a response to the way coloniality manifests itself in the United States and, second, by engaging Baldwin's response to colonialitythat is, decolonial loveas a religious response.